If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -42 = 0 Reorder the terms: -42 + -7x = 0 Solving -42 + -7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + -7x = 0 + 42 Combine like terms: -42 + 42 = 0 0 + -7x = 0 + 42 -7x = 0 + 42 Combine like terms: 0 + 42 = 42 -7x = 42 Divide each side by '-7'. x = -6 Simplifying x = -6
| 2(2X-2)=4(X-1) | | 11y+9=18 | | 7t-3=18 | | 15x+36=180y | | 4n+11n=n*(n+n) | | 7(m-28)-5(5m-39)=35 | | 7x+5x=12-8 | | -2(2x-3)=4x | | 7(x-6)+x=8(x-7)+14 | | 2x+4=x+5 | | (20x+4)+(15X+36)=180 | | 15x-7=10x+3 | | 2(7-6(1-n))+6n=-14+3(6(n+1)-3n) | | 7-n+16=20 | | 10z+5z+7z+5z+3z+8z+2z=2s+8s+3s+1s+4s | | -3y=2*-3-9 | | 2y+3y-4=8 | | 7-5u=-43 | | (-3*5)+(n*7)=-3*(n+7) | | 10+3x=-26 | | -3y=2x-9 | | -5(x+4)= | | 5(x-3)+4(x+3)=3(x-1) | | (n*5)+(n*3)= | | 8*1-4y=-12 | | 4(z+5)=32 | | 8*5+24= | | 8*-1-4y=-12 | | 8*-3-4y=-12 | | 6x-3y=12 | | 6x+10(2x)=132 | | 9(x-3)+6x=5(3x+2)-9 |